Positive Deviance (Better Evaluation)
Positive Deviance (PD) refers to a behavioral and social change approa ch which is premised on the observation that in any context, certain i ndividuals confronting similar challenges, constraints, and resource d eprivations to their peers, will nonetheless employ uncommon but succe ssful behaviors or strategies which enable them to find better solutio ns. Through the study of these individuals– subjects referred to as “p ositive deviants” - the PD approach suggests that innovative solutions to such challenges may be identified and refined from their outlying behavior.